Values behind Osong Kapali Ceremony: Sociocultural Review of Indigenous and Religious Tradition - Samiran, Fahmil; Elfiani, Elfiani; Daipon, Dahyul; Rahmiati, Rahmiati; Hendri, Hendri (UIN Maulana Malik Ibrahim Malang, 2022)
This study describes the domination of local custom and religion behind the tradition of Osong Kapali among Sungai Patai community in Tanah Datar, Minangkabau, Indonesia during the decease of Datuak (the leader of ethnic group). It employs a qualitative method with observation, interviews, and documentation as research instruments. It revealed, for people, that the majesty of datuak is reflected on not only the time he receive the tittle but also the time he passes away. This ceremony is intended to honor the dead datuak. The tradition begins with baretong (planning), mangkaji adaik (discussing the tradition), mancabiak kain kafan (tearing the shroud), osong kapali (putting on the traditional fabric), marocak (spreading the coin along the way to Datuak grave), pidato alam (welcoming speech), and manigo ari (praying after the funeral procession). It contains values within, such as the leader’s majesty, datuak wisdom, and symbols of broad and clean thought. In addition, it holds sharia, educational, and social values. Osong kapali tradition is a combination of custom and religion represented in the ceremonial sequences which agree with the ideology of sarak basandi kitabullah, the Quran-based tradition. Penelitian ini mendeskripsikan dominasi adat dan agama pada tradisi Osong Kapali yang dilakukan oleh masyarakat Nagari Sungai Patai kabupaten Tanah Datar di Minangkabau Indonesia ketika seorang datuak meninggal dunia. Penelitian ini menggunakan metode kualitatif melalui observasi, wawancara, dan dokumentasi sebagai instrumen penelitian. Hasil penelitian menunjukkan bahwa bagi masyarakat kebesaran seorang Datuak tidak hanya tergambar pada upacara pengangkatan gelar namun juga pada saat seorang datuak tersebut tutup usia. Upacara adat ini bertujuan untuk penghormatan kepada seorang datuak yang meninggal. Upacara Osong Kapali dimulai dengan baretong (Perencanaan), mangkaji adaik (mendiskusikan adat), mancabiak kain kafan (merobek kain kafan), Osong Kapali, pemasangan kain adaik (Pemasangan kain adat), maroncak (Menyebar koin sepanjang perjalanan ke kuburan Datuak), pidato alam (Pidato), dan manigo hari (berdoa setelah upacara pemakaman). Terdapat nilai nilai seperti kebesaran seorang pemimpin, kebijaksanaan seorang datuak dan symbol pemikiran yang luas dan bersih. Selain itu terdapat nilai teologi yakni nilai syari’ah, pendidikan dan sosial. Osong Kapali ini merupakan kombinasi antara adat dan agama yang terlihat dari rangkaian pelaksanaannya sesuai dengan filosofi adat ”sarak basandi kitabullah”.